Analisis dan Perancangan Sistem Informasi Penjualan dan Persediaan pada PT Nur Islami Tour and Travel - Titan, Titan; Luhukay, Devyano; Kurniawan, Yohannes (Bina Nusantara University, 2012)
The analysis and design of sales and inventory information system performed at PT Nur Islami is aimed to identify the organization needs to control and manage the data and information of operational transaction. The result will be used as a base for developing a new computerized system. The activity in analysis and design is focused in sales and inventory activities, which is the main core of the organization. These needs will be documented using unified modeling language. The C# and SQL Server 2005 will be used to design and develop the application and database for fulfilling the needs. This information system will ease the organization in doing their activity in selling and monitoring the stock. On the other hand, it will also minimize the data lost, which is usually caused by the conservative storage mechanism of transactional data.